PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN TAMU DI MANADO QUALITY HOTEL - Tombeng, Marthen; Sendow, Jelly; Makaminang, Jelni Y. (Jurnal Hospitaliti, 2023)
This study aims to determine the effect of service quality and price on guest satisfaction at Manado Quality Hotel. Guest satisfaction is an important factor in the hospitality industry because it can affect hotel reputation. The research method used is quantitative method with multiple linear regression data analysis techniques. The population in this study were guests at Manado Quality Hotel, with a sample of 30 people. The results showed that service quality has a significant effect on guest satisfaction at Manado Quality Hotel. Aspects such as staff friendliness, responsiveness to guest requests, room cleanliness, and the quality of hotel facilities have a positive impact on guest satisfaction. In addition, price also affects guest satisfaction. Prices that are reasonable and in accordance with the quality of service provided can increase guest satisfaction. Based on these findings, Manado Quality Hotel pays attention to and improves the quality of service provided to guests. Employee training in friendliness, responsiveness, and cleanliness can increase overall guest satisfaction. In addition, hotel management needs to consider pricing strategies that are competitive and in accordance with the value offered to guests. This research contributes to understanding the factors that influence guest satisfaction at Manado Quality Hotel. By understanding the effect of service quality and price, the hotel can take steps to improve guest satisfaction.